2005
DOI: 10.1177/0047244105051145
|View full text |Cite
|
Sign up to set email alerts
|

Introduction

Abstract: In the twenty years since Pierre Nora began publishing his landmark work on Les Lieux de mémoire (Nora, 1984-92), the study of memory, especially in its collective forms, has become a veritable industry. If historians such as Nora were to the fore in giving momentum to the field of study, scholars in many other disciplines have also been actively involved. It has become increasingly clear that the construction of memory is imbricated in a complex network of social, psychological, political and cultural process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…But as memory's stock rose, its nature and function became even more enigmatic. As Boutin et al (2005) observed,…”
Section: Memory and Countermemorysupporting
confidence: 72%
See 1 more Smart Citation
“…But as memory's stock rose, its nature and function became even more enigmatic. As Boutin et al (2005) observed,…”
Section: Memory and Countermemorysupporting
confidence: 72%
“…Restorative memory work should facilitate not only transmission from one generation to another but also jump across memory gaps where transmission has failed or was thwarted. Boutin et al (2005) referred to these gaps as "cognitive and ethical void(s) arising from irreparable loss" and pointed to the need to "mobilize an imaginary relation to the past for fundamentally different conceptions of the present" (p. 8). Repair and circulation of cultural memory to underwrite conservation of biological and cultural diversity can start with local historians and bards who are "relentless recorders" of an alternative past (Connerton 1989) or with ordinary men and women who hold on to their cherished seeds and commensal rituals and pass these along to their children.…”
Section: Conservation As Memory Workmentioning
confidence: 99%